Dampak Penutupan Selat Hormuz terhadap Geoekonomi dan Keamanan Geopolitik - Nur Syamsiah; Radimin Radimin (CV Global Research Publication, 2026)
The Strait of Hormuz plays a vital role in global energy security. This article aims to analyze the impact of the closure of the Strait of Hormuz on geoeconomics and geopolitical security. This study employs a qualitative research method based on a literature review approach. The research examines how the closure of the Strait of Hormuz affects both geoeconomic stability and geopolitical security. The findings indicate that disputes in the Strait of Hormuz are driven by differing interpretations of international maritime law under the 1982 United Nations Convention on the Law of the Sea (UNCLOS), particularly regarding the Transit Passage and Innocent Passage regimes, as well as Iran’s domestic legislation, namely the Marine Areas Act of 1993.From a geoeconomic perspective, the closure of the Strait of Hormuz could generate instability in global energy markets, leading to inflation, reduced purchasing power, and increased fiscal burdens on governments seeking to maintain domestic economic stability. Both oil- and natural gas-exporting and importing countries would be affected, resulting in disruptions across various sectors and dimensions of national development. From a geopolitical perspective, the closure of the Strait of Hormuz has the potential to escalate tensions among Middle Eastern countries and major global powers with strategic interests in the security of international energy routes. Such conditions may lead to an increased military presence, intensified competition for political influence, and a greater risk of broader regional or international conflict. Ultimately, the stability of the Strait of Hormuz remains a crucial factor in maintaining the balance of global geoeconomics and geopolitical security amid the increasingly complex dynamics of international relations.